Thermal Degradation Kinetics and Morphological Analysis of Poly-vinyl-butyral Cast Films Prepared with Various Organic Solvents - Abesach Moshalagae Motlatle; Lebohang Vivacious Mokoena (Chemical and Materials Sciences: Developments and Innovations Vol. 10, 2025)
Polyvinyl butyral (PVB) is an amorphous thermoplastic, produced through the reaction of polyvinyl alcohol with butyraldehyde in an acidic medium. The different groups are responsible for the physical and chemical properties of the polymer, including adhesiveness and viscoelasticity. Polyvinyl butyral (PVB) films are highly promising materials as they combine interesting thermal and structural morphology properties and in many cases coating viability. However, the polymerization ability of PVB films through solvent casting methods using different solvents is fundamentally not well understood. In this rationale, the present study demonstrates the use of Isopropanol, ethanol, methanol, and acetic acid for the development of high quality PVB films. The resulting acetic acid-based PVB film exhibits moderated thermal stability with smooth surface morphology which is an important factor in coating applications. On the other hand, ethanol-based PVB film achieves higher thermal stability relative to all other PVB films with some structural defects attributed to less impurities in the solvents. The paper shows a variety of solvents suitable with PVB for a range of applications in the coating industry. This study will pave the development of high-performance PVB cast films.